2012
DOI: 10.1007/s00464-012-2351-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of surgical plume among laparoscopic ultrasonic dissectors using a real-time digital quantitative technology

Abstract: BackgroundThis study aimed to analyze the effect of surgical plume generation from various ultrasonic dissectors on laparoscopic visibility, including the first cordless ultrasonic dissector, using a novel real-time digital quantification technique.MethodsThe Covidien Cordless Sonicision, the Harmonic ACE, and the Olympus SonoSurg were applied to bovine liver with industry-specified settings. Consecutive activations were digitally captured from a laparoscope positioned to replicate the clinical setting. Plume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 12 publications
0
32
1
Order By: Relevance
“…As an extension of this study, detection and quantification of surgical plume with ultrasonic dissectors using real-time digital quantitative technology ImageJ was pioneered by Kim et al [16]. The investigators reported that plume generation was increased in coagulation rather than in cut mode.…”
Section: Cordless Uss Improvises Agility and Handlingmentioning
confidence: 93%
See 4 more Smart Citations
“…As an extension of this study, detection and quantification of surgical plume with ultrasonic dissectors using real-time digital quantitative technology ImageJ was pioneered by Kim et al [16]. The investigators reported that plume generation was increased in coagulation rather than in cut mode.…”
Section: Cordless Uss Improvises Agility and Handlingmentioning
confidence: 93%
“…Deviation of the ACE from the Sonicision and SonoSurg was significant (p\0.05). There was a statistically significant difference in mean dissection speed and production of plume where Sonicision was resultantly shown to be faster in the tested tissue [16] ( Table 1).…”
Section: Cordless Uss Improvises Agility and Handlingmentioning
confidence: 97%
See 3 more Smart Citations